Carbon nanotube wools made directly from CO2 by molten electrolysis: Value driven pathways to carbon dioxide greenhouse gas mitigation. (September 2017) - Johnson, Marcus; Ren, Jiawen; Lefler, Matthew; Licht, Gad; Vicini, Juan; Liu, Xinye; Licht, Stuart
Abstract: A climate mitigation comprehensive solution is presented through the first high yield, low energy synthesis of macroscopic length carbon nanotube ("CNT") wool from CO2 by molten carbonate electrolysis. The CNT wool is of length suitable for weaving into carbon composites and textiles. Growing CO2 concentrations, and the concurrent climate change and species extinction, can be addressed if CO2 becomes a sought resource rather than a greenhouse pollutant. Inexpensive carbon composites formed from carbon wool as a lighter metal, textiles or cement replacement comprise major market sinks to compactly store transformed anthropogenic CO2 . 100×-longer CNTs grow on Monel versus steel. Monel, electrolyte equilibration, and a mixed metal nucleation facilitate the synthesis. CO2, the sole reactant in this transformation, is directly extractable from dilute (atmospheric) or concentrated sources, and the analyzed production cost of 660 per ton CNT is cost constrained only by the (low) cost of electricity. Today's market valuation of >100, 000 per ton CNT incentivizes CO2 removal. Highlights: Unusual carbon nanotube wools are introduced electrosynthesized in molten carbonate. C2CNT is CO2 transformation to carbon nanotubes by electrolysis in molten carbonate. (Air or exhaust) CO2 is the only reactant in C2CNT carbon nanotube wool synthesis. C2CNT product value (>100, 000) compared to cost (660) incentivizes CO2 removal. CO2 becomes a useful, valuable resource rather than a greenhouse gas pollutant.